Deletion of Viral microRNAs in the Oncogenesis of Epstein–Barr Virus-Associated Lymphoma - Kimura, Hiroshi; Okuno, Yusuke; Sato, Yoshitaka; Watanabe, Takahiro; Murata, Takayuki (Frontiers in Microbiology, 2021)
Epstein–Barr virus (EBV), which encodes >80 genes and nearly 50 non-coding RNAs, is a double-stranded DNA virus. EBV is associated with various types of lymphomas and lymphoproliferative disorders not only of B-cell but also T/NK-cell origin. However, the oncogenic mechanism remains poorly understood, including the EBV receptors expressed on T/NK cells, relationship of EBV with host genes, and epigenetic regulation of EBV and host genes. The roles of host and viral non-coding RNAs during tumorigenesis have been elucidated. EBV encodes at least 49 mature microRNAs (miRNAs), of which 44 are located in BamHI-A rightward transcripts (BARTs) region, and the remaining five are located in BamHI-H rightward fragment 1. BART miRNAs modulate cell differentiation, proliferation, apoptosis, and the cell cycle, and they are considered positive regulators of oncogenesis. We and others have recently reported that EBV-positive lymphomas frequently possess large deletions in BART miRNA clusters, suggesting that some viral miRNAs have suppressive effects on oncogenesis, and that deletion of these miRNAs may aid lymphoma formation.